Struktura obrazu – kształt myśli. Kognitywne aspekty średniowiecznych diagramów - Janowski, Jarosław; Rupiewicz, Romana (Vox Patrum, 2025)
Aristotle observed that the intellect operates using visual imagination, while Pseudo-Dionysius pointed to the possibility of representing the invisible through material forms. Nevertheless, since antiquity, the function of images has typically been understood as the depiction of an illusory appearance of existing things. In a broader context, this issue has always been present in philosophy—thinkers have pondered the nature of abstract concepts and their relation to the sensory world. Today, this subject is studied by cognitive psychology and cognitive science, both of which investigate how imaginative processes associated with abstract thinking function. Imagination forms the foundation for representing the "invisible." Cognitive science employs the theory of the embodied mind, which operates within a spatial environment. The idea of corporeality linked to space and its directions appears as early as Plato's Timaeus, and the ancient art of memory connected visual imagination with bodily sensations in space. This ancient practice of oratory masters is discussed at the beginning of the article. Subsequently, based on contemporary findings in cognitive science, the relationship between spatial experiences in logical thinking and the use of metaphors in linguistic and visual communication is analyzed. Detailed scientific insights into human cognitive faculties have been used to analyze selected medieval illuminations that employed Aristotle’s logic in visualizing conceptual knowledge. The findings reveal that medieval miniaturists demonstrated the power of visual thinking and the effectiveness of images in conveying and memorizing complex content.